1992
DOI: 10.1111/j.1365-2710.1992.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of 2 chemotherapeutic mouthrinses on the development of supragingival dental plaque and gingivitis

Abstract: Overholser CD, Meiiler TF, DePaola LG, Minah GE and Niehaus C: Comparative effects of 2 chemotherapeutic mouthrinses on the development of supragingival dental plaque and gingivitis. J Clin Periodontol 1990; 17: 575-579. Abstract. A 6-month double-blind, controlled clinical study was completed with 124 healthy adult subjects to determine the efficacy of 2 mouthrinses, Listerine (LA) and Peridex (PX), used as supplements to regular oral hygiene measures in reducing supragingival dental plaque and gingivitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 12 publications
13
93
1
2
Order By: Relevance
“…An essential oil-containing mouthrinse (EO) has demonstrated significant antiplaque and antigingivitis efficacy in short-term 7,8,9 and long-term clinical studies 6,10,11,12,13 designed within the guidelines required by the American Dental Association Council on Scientific Affairs for evaluating the clinical efficacy of chemotherapeutic mouthrinses.…”
Section: Introductionmentioning
confidence: 99%
“…An essential oil-containing mouthrinse (EO) has demonstrated significant antiplaque and antigingivitis efficacy in short-term 7,8,9 and long-term clinical studies 6,10,11,12,13 designed within the guidelines required by the American Dental Association Council on Scientific Affairs for evaluating the clinical efficacy of chemotherapeutic mouthrinses.…”
Section: Introductionmentioning
confidence: 99%
“…This data confirmed that rinsing regularly with an EOcontaining mouthrinse twice a day can reduce the level of blood-borne bacteria caused by a standardized challenge such as that of chewing an apple. It seems reasonable to assume that maintaining good oral hygiene practices, including tooth brushing, flossing and using an effective antimicrobial mouthrinse agent regularly, contributes to preventing periodontal disease, [7][8][9][10][11][12] which, in turn, leads to a lower risk of developing bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Essential-oil-containing mouthrinses (EOM) have shown anti-plaque and anti-gingivitis properties in short-7-9 and long-term clinical studies [10][11][12] designed according to the guidelines of the American Dental Association Council on Scientific Affairs. 13 Recently, Fine et al…”
Section: Introductionmentioning
confidence: 99%
“…Overholser et al (Overholser, et al, 1990) Chlorhexidine 0.12% Hydrogen Peroxide 1% Placebo 32 subjects ceased oral hygiene procedures, but rinsed, twice a day, with the designated mouthrinse for 21 days.…”
Section: Triclosan Not Available In the Us N/a Triclosanmentioning
confidence: 99%
“…Long-term reductions in plaque averaged between 45-61% and in gingivitis, 27-67% (Ciancio, 1989). Adverse effects reported may include staining of teeth, reversible desquamation, poor taste and alteration of taste and an increase in supragingival calculus (Flotra, et al, 1972, Overholser, et al, 1990). …”
Section: Chlorhexidinementioning
confidence: 99%